Structural Changes in the Forest Sector and Their Long-term Consequences for the Forest Sector - United Nations Economic Commission for Europe (United Nations, 2023)
The Forest Sector Outlook Study 2020-2040 (FSOS) for the UNECE region provides information that supports decision-making by showing the possible medium and long-term consequences of specific policy choices and structural changes, using scenario analyses whenever possible. The study is the first to cover the entire UNECE region and provides results for the main UNECE subregions of Europe, North America and the Russian Federation. These supporting Discussion Papers contain information on the possible impacts of future trends regarding the future forest carbon sink in tonnes of CO2 equivalents, and on harvest, production, consumption, net exports and prices of wood products by 2040. The study takes a pragmatic, transparent and objective approach to answering these key questions, sometimes using a modeling approach. It enables stakeholders to evaluate the long-term consequences of policy choices.